Efficacy of postoperative pain management in head and neck cancer patients - Ashley Hinther; Steven C. Nakoneshny; Shamir P. Chandarana; T. Wayne Matthews; Joseph C. Dort (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Our study quantifies the effectiveness of perioperative pain control in a cohort of patients undergoing major head and neck surgery with free flap reconstruction. Our long-term goal is to improve pain control and thereby increase mobility, decrease postoperative complications and decrease hospital stay. Methods A retrospective analysis was performed at a tertiary, academic head and neck surgical oncology program in Calgary, Alberta, Canada from January 1, 2015 – December 31, 2015. Pain scores were recorded prospectively. Primary outcomes were frequency of postoperative pain assessments and pain intensity using the numeric rating scale. Results The cohort included 41 patients. Analysis was limited to pain scores recorded from postoperative days 1–14. There was an average of 7.3 pain measurements per day (SD 4.6, range 1–24) with the most frequent monitoring on postoperative days 1–4. Median pain scores ranged from 0 to 4.5 with the highest median score on postoperative day 6. The daily maximum pain scores recorded ranged from 8 to 10 with scores of 10 recorded on postoperative days 1, 2, 3, 5, 7, 8, and 10. Patients most frequently had inadequate pain control on postoperative days 1, 2, 4, and 5 with the majority occurring on postoperative day 1. Conclusions Postoperative pain control could be improved at our centre. The frequency of pain assessments is also highly variable. Ongoing measurement, audit, and feedback of analgesic protocol effectiveness is an excellent first step in improving perioperative pain management in patients undergoing major head and neck cancer surgery with free flap reconstruction.